Multi‐Center Retrospective Evaluation of Screw and Polymethylmethacrylate Constructs for Atlantoaxial Fixation in Dogs. Issue 7 (1st September 2016) - Stout Steele, Megan W.; Hodshon, Amy W.; Hopkins, Andrew L.; Tracy, Gaemia M.; Cohen, Noah D.; Kerwin, Sharon C.; Boudreau, C. Elizabeth; Thomas, William B.; Mankin, Joseph M.; Levine, Jonathan M.
Abstract : Objective: To evaluate outcome and adverse events following ventral stabilization of the atlantoaxial (AA) joint in dogs with clinical AA subluxation using screw/polymethymethacrylate (PMMA) constructs in a retrospective, multi‐center cohort study. Study Design: Historical cohort study. Animals: 35 client‐owned dogs. Methods: Medical records from 3 institutions were reviewed to identify dogs with AA subluxation treated with ventral screw and PMMA constructs. Data on signalment, pre‐ and postoperative neurologic status, imaging performed, and adverse events were retrieved. Neurologic examination data were abstracted to generate a modified Frankel score at admission, discharge, and re‐examination. Telephone interview of owners >180 days postoperative was conducted. Results: Thirty‐five dogs with AA subluxation treated with ventral screw/PMMA constructs were included. Most dogs were young (median age 1 year), small breed dogs with acute onset of neurologic signs (median duration 22.5 hours). Most dogs were non‐ambulatory at the time of admission (median modified Frankel score 3). Adverse events were identified in 15/35 dogs including 9 dogs with major adverse events. Four dogs required a second surgery due to vertebral canal violation (n = 2) or implant failure (n = 2). Re‐examination at 4–6 weeks postoperative reported 15/28 dogs with improved neurologic status and 19/28 dogs were ambulatory. Telephone follow‐up was available for 23/35 dogs with 23/23 reported as ambulatory (median follow‐up 390 days). Conclusions: Ventral application of screw and PMMA constructs for AA subluxation, as described here, is associated with clinical improvement in the majority of dog. Major adverse events are infrequent and the technique is considered relatively safe.